꾸지뽕나무 열매에서 추출한 4’-O-methylalpinumisoflavone의 항산화 및 미백 효과 - 류지효(Ji Hyo Lyu); 노준용(Joon Yong Noh); 김수라(Sura Kim); 이금산(Guem San Lee); 이동호(Dongho Lee); 김관회(Koanhoi Kim); 김형우(Hyungwoo Kim) (동의생리병리학회지, 2019)
The anti-inflammatory effects of 4'-O-methylalpinumisoflavone (OMAI) has been reported in recent years. To develop effective and safe skin whitening agents, we investigated the anti-oxidative and melanogenic effects of OMAI isolated from fruit of Maclura tricuspidata Carrière (Cudrania tricuspidata) in macrophage and melanoma cell lines. In our results, OMAI showed effective superoxide scavenging activity and suppressed production of lipopolysaccharide (LPS)-induced intracellular reactive oxygen species (ROS) in RAW264.7 cells. In addition, α-melanocyte stimulation hormone (MSH)-induced production of melanin was also reduced by OMAI in B16F10 cells. Finally, OMAI significantly inhibited tyrosinase activity in B16F10 cells. These results suggest that OMAI suppressed melanin production via scavenging reactive oxygen species and inhibition of tyrosinase activity.